2007
DOI: 10.1167/iovs.06-1054
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cholesterol Homeostasis by Antiproliferative Drugs in Human Pterygium Fibroblasts

Abstract: Intracellular modifications of cholesterol homeostasis may be relevant to pterygium development. Moreover, antiproliferative agents such as PIO and EVE may represent a potential topical medication in the prevention and inhibition of pterygium growth at an early stage, probably by modulation of cholesterol ester metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…We moreover demonstrated that cholesterol esterification in smooth muscle cells is a key event in vascular proliferative diseases [20]. Furthermore, inhibition of CEs synthesis partially blocked cell proliferation, although the extent of the latter effect was dependent on the cell type [20][21][22][23], suggesting the potential involvement of cholesterol esterification as a new pathway implicated in cell growth. On the other hand, several studies have demonstrated how proliferation of tumour cells is arrested in a delipidated medium, with inhibition being almost completely prevented following addition of LDL and/or HDL [24,25].…”
Section: Introductionmentioning
confidence: 81%
“…We moreover demonstrated that cholesterol esterification in smooth muscle cells is a key event in vascular proliferative diseases [20]. Furthermore, inhibition of CEs synthesis partially blocked cell proliferation, although the extent of the latter effect was dependent on the cell type [20][21][22][23], suggesting the potential involvement of cholesterol esterification as a new pathway implicated in cell growth. On the other hand, several studies have demonstrated how proliferation of tumour cells is arrested in a delipidated medium, with inhibition being almost completely prevented following addition of LDL and/or HDL [24,25].…”
Section: Introductionmentioning
confidence: 81%
“…37 Everolimus and pioglitazone, drugs that alter the metabolism of cholesterol, have been shown to decrease pterygia fibroblasts proliferation, as well as the levels of molecules involved in the regulating intracellular cholesterol homeostasis acyl-coenzyme A cholesterol acyltransferase and multidrug resistance protein. 39 The results of these studies suggest the use of topical drugs in the prevention of pterygium proliferation by the modulation of cholesterol ester metabolism.…”
Section: Alterations In Cholesterol Metabolismmentioning
confidence: 94%
“…[8][9][10] Alternatively, a wide array of pathogenic factors has been proposed, including viral infections, 11 epigenetic aberrations, 12-14 epithelialmesenchymal transition, 15,16 immunologic [17][18][19][20] and anti-apoptotic mechanisms, 21-24 angiogenic 2,25,26 and lymphangiogenic stimulation, 27,28 deregulation of extracellular matrix modulators 4,29 and growth factors, 30 inflammation cascades, 31-33 recruitment of bone-marrow-derived stem and progenitor cells, [34][35][36] and modifications in cholesterol metabolism. [37][38][39] However, most of these factors are more related to the development and maintenance of the disease than to its origin. It has been shown that some of these factors are directly or indirectly related to UV radiation exposure, as will be discussed further.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have proposed that accumulation of CE spares energy needed for de novo sterol synthesis, allowing greater proliferation and migration and perhaps a quicker return to growth after a period of stasis (Batetta, Pani et al 1999;Antalis, Arnold et al 2010;Antalis, Uchida et al 2011). The process of cholesterol esterification was linked to proliferation in multiple studies in different cancer cell lines (Batetta, Pani et al 1999;Peiretti, Dessi et al 2007;Paillasse, de Medina et al 2009;Antalis, Arnold et al 2010;Mulas, Abete et al 2011), implying a complex network of signaling pathways and gene expression that ties cholesterol accretion to tumorigenesis. However, the exact role of CE in tumorigenesis remains to be determined.…”
Section: Experimental and Mechanistic Evidence For Role Of Ldl In Cancermentioning
confidence: 99%